Magnetization, resistivity, specific heat and ab initio calculations of Gd5Sb3. (26th June 2018) - Samatham, S Shanmukharao; Patel, Akhilesh Kumar; Lukoyanov, A V; Suresh, K G
Abstract: We report on the combined results of the structural, magnetic, transport and calorimetric properties of Mn5 Si3 -type hexagonal Gd5 Sb3, together with ab initio calculations. It exhibits a ferromagnetic (FM)-like transition at 265 K, antiferromagnetic (AFM) Néel transition at 95.5 K followed by a spin-orientation transition at 62 K. The system is found to be in AFM state down to 2 K in a field of 70 kOe. The FM-AFM phase coexistence is not noticeable despite large positive Curie–Weiss temperature ( K). Instead, low-temperature AFM and high-temperature FM-like phases are separated in large temperatures. Temperature-magnetic field ( H - T ) phase diagram reveals field-driven complex magnetic phases. Within the AFM phase, the system is observed to undergo field-driven spin-orientation transitions. Field-induced tricritical and quantum critical points appear to be absent due to the strong AFM nature and by the intervention of FM-like state between paramagnetic and AFM states, respectively. The metallic behavior of the compound is inferred from resistivity along with large Sommerfeld parameter. However, no sign of strong electron-correlations is reasoned from the Kadowaki–Wood's ratio cm · (mol · K) 2 (mJ) −2, despite heavy γ . Essentially, ab initio calculations accounting for electronic correlations confirm AFM nature of low-temperature magnetic state in Gd5 Sb3 and attainable FM ordering in agreement with experimental data.